Improving of 6 weeks of repeated sprint training on the aerobic and anaerobic power of college-age male rugby players - Wang, Shuo; Tang, Jiakai; Liu, Shuning; Li, Huixin; Li, Qian; Pan, Liang; Chen, Zezhao; Liu, Chang (Frontiers in Physiology, 2025)
BackgroundRugby is characterized by the necessity for athletes to engage in high-intensity efforts followed by rapid recovery phases. Effective training methodologies that enhance both aerobic and anaerobic capacities are crucial for peak athletic performance in this sport. Objective: This study aimed to assess the efficacy of a 6-week repeated sprint training (RST) program in enhancing the aerobic and anaerobic power of collegiate male rugby players, compared to high-intensity interval training (HIIT).MethodsTwenty-eight male collegiate rugby players were randomly assigned to one of two groups: repeated sprint training group (RSTG) or a high-intensity interval training group (HIITG). Aerobic power was assessed using the Yo-Yo IR1 Test and an incremental load gas metabolism test, while anaerobic power was measured through the Wingate Anaerobic Test. Assessments were conducted pre- and post-intervention.ResultsAll participants completed the study, and all data were included in the analysis. Mixed repeated measures ANOVA revealed significant main effects of time on the Yo-Yo IR1 test, VO2max, VT-VO2, VT/VO2max, LA10, peak power (PP), and mean power (MP), indicating significant improvements in both groups post-intervention compared to baseline. Additionally, the time × group interaction effect was significant for VT-VO2 and LA10. Further paired samples t-test analysis showed that, compared to the HIIT group (HIITG), the repeated sprint training group (RSTG) demonstrated greater intervention effects on Yo-Yo IR1, VO2max, VT-VO2, VT/VO2max, LA10, PP, and MP, with more stable improvements.ConclusionThe 6-week RST protocol was more effective than HIIT in improving key aerobic and anaerobic capacities in collegiate male rugby players. These findings advocate for the integration of RST into the training schedules of rugby players to optimally enhance performance-related physical attributes.